The Evaluation of Large, Complex UML Analysis and Design Models - Berenbach, Brian (International Conference on Software Engineering: Proceedings of the 26th International Conference on Software Engineering; 23-28 May 2004, 2004)
This paper describes techniques for analyzing largeUML models. The first part of the paper describesheuristics and processes for creating semantically correctUML analysis and design models. The second part of thepaper briefly describes the internal DesignAdvisorresearch tool that was used to analyze Siemens models.The results are presented and some interestingconclusions are drawn.